Health in All Policies. Ein Ansatz um für die Integration von SDG 3 und SDG 11 zu lernen?! Überlegungen anhand von Walkability mit einer Nord-Süd-Perspektive. - Baumgart, Sabine; Köckler, Heike (Taylor & Francis, 2021)
Health in All Policies (HiAP) is an approach of the World Health Organisation (WHO) that has been pursued since the 1980s. The overall goal of this approach is to achieve health promotion, prevention and health care for all people by using the potential of all policy fields. This article aims to specify the global guiding principles HiAP and SDGs through an integrated perspective and a North-South dialogue. Referring to SDG 3 “good health and well-being” and SDG 11 “sustainable cities and communities” the focus is first on health-related aspects of spatial planning and the concept of walkability as an integrating approach. The contribution starts with an integrated mobility- related consideration of SDG 3 and 11 by elaborating on the concept of walkability in relation to spatial planning in the context of health-promoting urban development. Walkability addresses movement-oriented locomotion and thus contributes to physical activity, which promotes health and leads to sustainable transport systems (SDG 11.2). It is also a topic that is part of the WHO’s Global Action Plan on Physical Activity. Furthermore it will be discussed to what extent this concept, which refers to cities in the Global North, can also be transferred to cities in the Global South, and conclusions will be drawn.
Keywords: Nachhaltige Stadtentwicklung; Integrierte Stadtentwicklung; Gesundheitsförderung; Stadtgestaltung; Aufenthaltsqualität; Erreichbarkeit; Fußgängerverkehr; Fahrradverkehr; Sustainable Development Goals